E-033 Bow Hunter's syndrome: an unusual cause of symptomatic vertebral artery stenosis. (4th July 2012) - Miller, D; Tawk, R; Barrett, K
Abstract : Introduction/purpose: Bow Hunter's syndrome is an unusual symptomatic vertebral artery syndrome resulting from intermittent mechanical compression of the vertebral artery. We describe a case of symptomatic left vertebral artery compression diagnosed by dynamic cerebral angiography and discuss the pathophysiology, diagnosis, and treatment of this unusual syndrome. Materials/methods: A 44-year-old right-handed male was transferred to Mayo Clinic hospital after being admitted to an outside hospital with left-sided weakness and numbness and difficulty with balance. The patient became symptomatic while driving his truck on the highway about 10 days before. An outside MRI confirmed an acute CVA involving the cerebellum and left medulla. An MR angiogram suggested stenosis of the left vertebral artery in the mid cervical region. Cerebral angiography revealed only mild stenosis of the left vertebral artery in the neutral position. Angiograms with the patient had turned to the left revealed almost complete occlusion of the left vertebral artery. Turning the head to the right essentially completely resolved the stenosis. CT angiography with three-dimensional reconstruction confirmed a large uncovertebral spur encroaching on the foramen transversarium at C5-6. Results: The patient was evaluated for endovascular therapy verses open surgical treatment. He was treated with anterior cervical discectomy and fusion with surgical excision of the spur. This resulted in complete resolution of his symptoms. Conclusions: Bow Hunter's syndrome is an unusual mechanical entrapment syndrome of the vertebral artery which can be difficult to diagnose with conventional non-invasive imaging. Dynamic cerebral angiography can lead to an appropriate diagnosis. Treatment can be surgical or endovascular, and can lead to complete resolution of symptoms. Competing interests: None.